Management Accounting For Business - Drury, Colin (Andover : Cengage Learning, 2009)
Aimed at non-accounting management students, this textbook offers a thorough introduction to management accounting, approaching the subject from a managerial perspective, without sacrificing accuracy or detail.
Previous ed.: London: Thomson Learning, 2005.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Managerial accounting; Managerial accounting -- Problems, exercises, etc